2017
DOI: 10.1002/slct.201602044
|View full text |Cite
|
Sign up to set email alerts
|

AIE Active Carbazole-Benzothiazole Based ESIPT Motifs: Positional Isomers Directing the Optical and Electronic Properties

Abstract: Three positional isomers based on carbazole (Cz) and hydroxy benzothiazole (HBT) were synthesized targeting solid state organic emitters by Suzuki coupling reaction and their optical, structural and electronic properties were compared. The changing of position of HBT unit on 9‐phenyl‐9H‐carbazole alters the optical and structural properties significantly. The synthesized compounds are highly emissive in solid and aggregated state (Φf=∼ 40 %) and weakly emissive in solvents of different polarities (Φf=2.6‐17 %)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Certain 2‐naphthol tethered Schiff bases show fluorescence emissions due to excited state intramolecular proton‐transfer and the intensity of emission in each case was enhanced upon addition of water. It is also suggested that ESIPT and AIE took place in those hydroxy‐aromatic imines and the emissions were dependent on the concentration of water . Based on these one may suggest that the emission occurring at the 446 nm of 2‐hydroxynaphthaldoxime upon addition of water is due to a combine effect of ESIPT and AIE.…”
Section: Resultsmentioning
confidence: 97%
“…Certain 2‐naphthol tethered Schiff bases show fluorescence emissions due to excited state intramolecular proton‐transfer and the intensity of emission in each case was enhanced upon addition of water. It is also suggested that ESIPT and AIE took place in those hydroxy‐aromatic imines and the emissions were dependent on the concentration of water . Based on these one may suggest that the emission occurring at the 446 nm of 2‐hydroxynaphthaldoxime upon addition of water is due to a combine effect of ESIPT and AIE.…”
Section: Resultsmentioning
confidence: 97%
“…Another widely used backbone that is used to construct ESIPT‐based AIEgens is 2‐(2′‐hydroxyphenyl)benzothiazole (HBT, Scheme 2I with X = S), which is a typical ESIPT fluorophore bearing an intramolecular hydrogen bond O─H···N and show AIE properties by virtue of RIM mechanism. [ 31, 36, 42, 45, 46, 56, 59, 63, 73, 76, 81, 100, 103, 108, 120–123, 126, 131 , 180–194 ] The emissions of HBT derivatives are easily tunable and extended to the red region, making them advantageous to be applied in bioimaging. [ 103, 126, 192, 193, 195 ] In addition, a few of ESIPT‐based AIEgens based on 2‐(2′‐hydroxyphenyl)benzimidazole (HBI, Scheme 2I with X = NH), [ 196 ] and 2‐(2′‐aminophenyl)benzothiazole (ABT, Scheme 2J) [ 52, 63, 90, 101, 114, 197 ] have been reported.…”
Section: Backbones Of Esipt‐aie Luminogensmentioning
confidence: 99%
“…They are strongly emissive in the green region. The PLQY reaches 0.38 for 47, but is lower for the other two compounds, due to conformational differences [75]. [75], 50 [52], 51 [77] and 52 [78] with solid-state PL maxima (λ em ) and photoluminescence quantum yields (Φ PL ).…”
Section: Carbazole Derivatives: Electroluminescence and Gelsmentioning
confidence: 99%
“…Figure 15. Molecular structure of carbazole derivatives 47−49[75], 50[52], 51[77] and 52[78] with solid-state PL maxima (λ em ) and photoluminescence quantum yields (Φ PL ).…”
mentioning
confidence: 99%